Safety evaluation of Aspergillus fumigatus grown on cassava for use as an animal feed - Khor, G. L.; Alexander, J. C.; Lumsden, J. H.; Losos, G. J. (Canadian Veterinary Medical Association, 1977)
A safety evaluation of A. fumigatus I21, grown in a cassava carbohydrate and salts medium, was undertaken. Male weanling rats were fed the fungus at 20, 30 and 40% of the diet for 90 days. A control group was given soybean oil meal as the sole source of protein. Weekly determinations of the body weights and feed consumptions were made. A few days prior to termination of the feeding study, a kidney function test was undertaken on the rats. At the end of the feeding period hematology, blood biochemistry, urine analyses and histopathology studies of various tissues were carried out, and organs were weighed. Rats fed A. fumigatus I21 gained less weight than the controls, but kidney weights were increased. Increases in serum alkaline phosphatase and glutamic-oxaloacetic transaminase were not related to dose level. The blood urea nitrogen was increased for the rats fed 40% of the fungus. Rats fed 30 and 40% of the fugus I21 showed a significant drop in albumin. Deficiency in methionine or other essential amino acids through a limited feed consumption may have caused a decrease in albumin synthesis. Rats fed the highest level of the fungus showed increases in neutrophils and monocytes concomitant with decreases in lymphocytes and eosinophils which may be a response to stress. The urine analyses did not reveal any significant differences. The test rats were capable of concentrating urine adequately when deprived of water for 24 hours. No significant differences between the control and experimental groups were found by histopathological examinations.